Study of the vasodilatory effect of extract from tissue culture biomass of Rauwolfia serpentina Benth. - I. L. Monchak; I. I. Konvalyuk; А. О. Balanda; S. S. Lukashov; V. I. Matiushok; V. A. Kunakh; S. M. Yarmoluk; A. I. Soloviev (The State Expert Center of the Ministry of Health of Ukraine, 2021)
Design of novel herbal drugs with a wide range of activity is an important object of pharmacology. Herbal remedies having antiarrhythmic, cardiotonic and vasodilatory effects are useful for treatment of heart arrhythmias. Vasodilating drugs are prescribed for medication of hypertension and migraine. Also they are a part of comprehensive treatment of various diseases such as disturbed peripheral blood circulation and atherosclerosis of arteries of extremities as well as problems with urination and potency. Search for novel herbal preparations with vasorelaxant activity in our view is a promising matter of current interest. This work is aiming in study of vasodilatory activity of methanol extract of strain K-27 tissue culture of Rauwolfia serpentina. Evaluation of vasodilatory activity extract of high-productive strain K-27 tissue culture of Rauwolfia serpentina has been carried out by the method of auxotonic mechanography of vascular smooth muscles. Strength and frequency of spontaneous contractions of portal vein as well as relaxation of aortic smooth muscles activated with phenylephrine were evaluation indicators of extract activity. In order to estimate working concentration of extract of strain K-27 tissue culture of Rauwolfia serpentina we have studied vascular activity at sequentially increasing concentrations of extract solution on the portal vein. Overlay of sequence of growing concentrations exhibited decrease in basal level of venous tone and dose-dependent suppression of phasic contractions with complete inhibition of spontaneous activity of portal vein at 1.44 mg/ml concentration and uprise of toxicity at higher concentrations. It has been shown dose-dependent relaxation of vascular preparations followed by development of α-adrenoceptor blocking effect and loss of sensibility to phenylephrine at the end of experiment. After discontinuing exposure with a substance the activating effect of phenylephrine remained not renewed during 30-50 minutes, at the same time contractile activity of aorta on the response to the other type activation (60 mM K+) took place. It was found that at the studied range of concentrations: 0.0288 μg/ml-28.8 μg/ml the extract of strain K-27 tissue culture of Rauwolfia serpentina has distinct vasodilatory effect. Also it was discovered α-adrenoceptor blocking effect of that extract, so it can find wide application in therapy as vasorelaxant and α-blocker, for instance in treatment of prostate diseases.